Online shopping behaviour : a case study of Singapore. - Lee, Amy Yee Min. (2009)
This study investigates the relationship motivational factors (convenience, brand variety, price, and price negotiation) behind online shopping behaviour in Singapore, between purchase decision and information attributes (buyer-search, user feedback, buyer-seller communication) and between information asymmetry and buyer-search. A total of 8 hypotheses were developed. The objectives were achieved using data collected from selfadministered survey through convenience sampling. A total of 192 useful surveys were received. Findings revealed that buyer-search and online feedback are highly valued by Singaporean online shoppers while other attributes have little influence on online purchase of Singaporeans. Gender also affects online purchase. Information asymmetry has little influence on buyer-search behaviour of online shoppers. Managers were recommended to implement feedback mechanisms on their websites and strategise to create non-monetary values for online shoppers and not overlook the importance of a physical store. Gender-specific businesses should also alter their strategies accordingly. The limitations of the study were the inability to draw causal relationships between the variables with online purchase due to its descriptive nature. Time constraint limited the depth of this study. This study could be expanded for future research by including more hedonic aspects of online shopping and explore the changes in values when an online shopper shops online and at physical stores to further understand online shoppers.